Fast 'wandering' Takotsubo syndrome: atypical mixed evolution from apical to mid-ventricular ballooning. (November 2017) - Casavecchia, Grazia; Zicchino, Stefano; Gravina, Matteo; Maulucci, Guglielmo; Manuppelli, Vincenzo; Tarantino, Nicola; Ruggiero, Antonio; Russo, Dolores; Santoro, Francesco; Macarini, Luca; Biase, Matteo Di; Brunetti, Natale Daniele
We report the case of a 53-year-old woman admitted for typical chest pain and a diagnosis of Takotsubo syndrome (TTS). Initial echocardiographic presentation was characterized by apical and mid-ventricular akinesis and basal hyper-kinesis. Unexpectedly, later after admission, echocardiography showed recovered apical akinesis with an apparent 'migration' of systolic dysfunction to mid-ventricular segment and hyper-kinesis of apical and basal segments. One week after admission, left ventricular contractility completely recovered and cardiac magnetic resonance imaging did not show signs of subendocardial late-enhancement and myocardial edema. Cases of TTS may therefore occasionally rapidly 'wander' within left ventricular segments, raising doubts over the so far used classification of left ventricular patterns of ballooning in subjects with TTS (typical/atypical). Apparently, different patterns can rapidly evolve into each other. The absence of late-enhancement at cardiac magnetic resonance imaging could hypothetically identify rapidly 'wandering' cases.